Effect of dolutegravir on weight changes and lipid profile compared with efavirenz in people living with HIV: A retrospective cohort study - Rachawit Setpakdee; Sasisopin Kiertiburanakul (Journal of Infection and Public Health)
Background: There are limited data on DTG-associated weight gain among treatment-naïve Asian people living with HIV (PLHIV). Methods: Eighty-one and 100 PLHIV initiating DTG-based and efavirenz (EFV)-based antiretroviral therapy (ART), respectively, were retrospectively investigated for weight changes and lipid profiles at 6 and 12 months after ART initiation. Results: At baseline, the DTG group had a lower mean body weight (BW) (60.7 kg vs. 64.3 kg, p = 0.071) and lower mean cholesterol level (172 mg/dL vs. 185 mg/dL, p = 0.029) than the EFV group. Mean BW remained lower in the DTG group than in the EFV group at 6 [58.2 kg vs. 66.0 kg, mean difference (MD) −7.8, p = 0.005] and 12 (59.6 kg vs. 67.0 kg, MD −7.3, p = 0.008) months. BW did not significantly change between baseline and 12 months in the DTG group (60.7 kg vs. 59.6 kg, p = 0.495), whereas it significantly increased between baseline and 12 months in the EFV group (64.3 kg vs. 66.9 kg, p = 0.019). Cholesterol levels did not significantly increase between baseline and 12 months in either group. After adjustment, DTG use [MD −5.85, 95 % confidence interval (CI) −10.45, −1.24, p = 0.013] and baseline BW (MD 0.97, 95 % CI 0.79, 1.15, p < 0.001) were significantly associated with BW changes over time. Conclusions: DTG-based ART was not significantly associated with increased BW and cholesterol levels compared with EFV-based ART in treatment-naïve Thai PLHIV.